pH-Responsive Tamoxifen-LoadedPoly(ε-caprolactone)/Poly(vinylpyrrolidone)/Poly(ethyleneoxide) Fibers for Treatment of Breast Cancer: Investigation of ControlledDrug Release Properties - Pekdemir, Sibel Selcuk; Ulu, Oznur Dogan; Ulu, Ahmet; Pekdemir, Mustafa Ersin; Kurucay, Ali; Ates, Burhan (Amer Chemical Soc, 2026)
Herein, this study reports the production of fiber mats obtained by electrospinning, produced by mixing tamoxifen (TAM) drug with polycaprolactone (PCL), polyvinylpyrrolidone (PVP), and poly(ethylene oxide) (PEO), with the aim of eliminating cancer cells through controlled drug release. The fabricated fiber mats were thoroughly characterized by several analytical techniques. FTIR analysis indicated strong intermolecular interactions between polymer molecules of the fiber. XRD analysis revealed that fibers are semicrystalline in nature. Scanning electron microscopy verified the uniform nanofibers with bead-free morphology and the average fiber diameter ranged from 346 to 418 nm with drug loading. An increase in tensile strength (TS) and elongation at break (EAB) values of the fibers was observed after drug loading. TS and EAB was obtained up to 0.35 MPa and 88.69%, which are desired for the application. The release of TAM from the fabricated fibers strongly depended on pH value and the drug was fully released in 100 h at pH 5.5. Moreover, Higuchi, Hixson-Crowell, and Korsmeyer-Peppas kinetics confirmed the controlled release of the drug from the fiber mats via diffusion. After 24, 48, and 72 h, the cell viability rates in L929 cells were determined to be 69.7%, 88.5%, and 63.7%, respectively, while cell viability rates were calculated as 69.9%, 68.9%, and 57.7%, respectively, in MCF-7 cells. Additionally, acridine orange (AO)/ethidium bromide (EB) staining was used to detect apoptosis, and fluorescent staining images revealed apoptotic effects. Taken together, these findings suggested that the produced fiber mats could be a promising candidate for controlled TAM release in breast cancer treatment.
Keywords: Drug-Release; Tamoxifen